The impact of institutions on income inequality in the EU Member States - Jianu, Ionuț; Tudorache, Maria-Daniela (European Journal of Sustainable Development, 2025)
This paper aims to analyse the influence of institutional quality on income inequality across the 27 EU Member States during the period 2011-2022. To achieve this, we employed the Panel Estimated Generalized Least Squares (EGLS) method. Our findings demonstrate that enhancing institutional quality-measured through key institutional factors published by the World Bank under the Good Governance Indicators, such as political stability, regulatory quality, and government efficiency - plays a significant role in reducing income inequality. Furthermore, the study confirms a strong positive correlation between the unemployment rate and income inequality, with additional social factors, such as early school leavers and housing cost overburden, that further exacerbate inequality. Conversely, an increase in government spending on social protection appears to mitigate these disparities. Additionally, we identify a strong inverse relationship between income inequality and human development. The robustness of our model has been validated, reinforcing confidence in the reliability of the estimated parameters and the study’s overall conclusions. Keywords: Institutions, Human Development, Income Inequality, Government efficiency, Political stability, Regulatory quality